Partisipasi masyarakat dalam perencanaan APBDes Sasakpanjang Kecamatan Tajurhalang Kabupaten Bogor - Heru Cahyono; Kurniasih Mufidayati (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2021)
Community participation in the formulation of APBDes is one of the determining factors for villages in achieving the autonomy and prosperity since the law number 6 of 2014 concerning Villages was issued. How Sasakpanjang villagers participate in APBDes formulation is an issue that wants to be clarified through this research. Knowing this can be used to improving policy in the APBDes planning. This study uses the participation ladder from Arnstein. Combined with participatory budgeting theory by Wampler.Method of this study uses a qualitative approach with a descriptive carried out in Sasakpanjang Village, Bogor Regency. The informants in this study were selected purposively. The sample of data sources chosen purposively. Data collection is done through document review and in-depth interviews. Analysis and test of the validity of the data is done through, coding and categorization interview transcripts, interim conclusions, triangulation/crosscheck, and final conclusions. This study has resulted that quality of community participation in Sasakpanjang village at the damping level in the tokenism degree. Communities have begun to have an influence on the APBDes policy, but its nature is still artificial, and has not been able to control the APBDes policy. The inhibiting factors include, weak village government institutions, lack of leadership, and community characteristics. Therefore, village assistance needs to be reoriented. Abstrak Partisipasi masyarakat dalam perumusan kebijakan Anggaran Pendapatan dan Belanja Desa (APBDes) menjadi salah satu faktor yang menentukan bagi desa dalam mencapai kemandirian dan kesejahteraannya. Penelitian ini bertujuan mengetahui bagaimana masyarakat desa Sasakpanjang berpartisipasi dalam perumusan APBDes-nya. Faktor apa yang menghambat partisipasi masyarakat penting untuk diketahui. Penelitian ini merujuk pada teori tangga partisipasi dari Arnstein dan teori penganggaran partisipatif Wempler. Metode penelitian yang digunakan kualitatif deskriptif. Data diperoleh dari telaah dokumen dan indepth interview. Kesimpulan penelitian ini, kualitas partisipasi masyarakat desa Sasakpanjang masih pada level peredaman dalam degree of tokenism. Masyarakat sudah mulai mempunyai pengaruh terhadap kebijakan APBDes, tetapi bersifat artifisial dan belum mampu mengontrol kebijakan APBDes. Faktor-faktor yang menghambat antara lain, lemahnya institusi pemerintahan desa, ketiadaan leadership, budaya masyarakat dan praktik pendampingan desa yang perlu reorientasi karena masih bersifat administratif.